Cross-cultural dimensions influence on business internationalization by soft computing technique. (October 2017) - Sokolov Mladenović, Svetlana; Mladenović, Igor; Milovančević, Miloš; Denić, Nebojša
Abstract: Cultural difference plays an important role in industrialized business countries. The topic of cross-cultural management has become the topical area in modern business worldwide. Cross-cultural implication and cultural dimensions was analyzed using Hofstede model that consists of seven dimensions: Assertiveness, Future Orientation, Performance Orientation, Power Distance, Uncertainty Avoidance, Collectivism I (Institutional) and Collectivism II (In-Group). In the present paper, we investigate what impact business internationalization has on cross-cultural dimensions - specifically, gender egalitarianism forecasting and humane orientation. A soft computing method was applied for this analyzing. Combination of Collectivism I (Institutional) and Collectivism II (In-Group) was the most influential on the Gender Egalitarianism and the combination of Future Orientation and Performance Orientation was the most influential on the Humane Orientation in the business internationalization. Highlights: Cultural difference plays an important role in business internationalization. Cross-cultural management has become the topical area in business internationalization. Cross-cultural implication and cultural dimensions was analyzed using Hofstede model.